"If You Will Only Remain in This Land" Migration Decision Making and Jeremiah as a Religiously Motivated Nonmover - Trinka, Eric ca. 20./21. Jh. (2018)
The last two decades have witnessed a steady increase in the application of social-scientific methodologies to the text of Jeremiah. Biblical scholars have employed migration studies, along with other transdisciplinary models, as a heuristic framework for exploring the forced relocations of Judahite populations described in the text. Despite much good work in these areas, biblical scholars still struggle to appropriately integrate important foundational concepts from geographic studies as well as recent and relevant data from migration studies. To fill this lacuna, I provide evidence of migrant decision-making processes in order to present a nuanced understanding of migrational realities represented in the text of Jeremiah. Consideration of the variables of a people's long-term exposure to violence and their religious dispositions/affiliations in tandem with the geographic concepts of place utility and duration dependence provides a coherent model for more accurately describing the representations of Jeremiah's experiences in chaps. 39-43. The text of Jeremiah represents rather well several realities of migrant decision-making processes. I argue that Jeremiah's actions can best be described as those of a religiously motivated nonmover.
Keywords: Bible. Jeremiah; Decision Making; Forced Migration; Jeremiah; Population transfers; Victims of violent crimes; duration dependence; Exile; Forced Migration; migration decision making; Religion